HIV-1 Reverse Transcriptase Inhibition by Major Compounds in a Kenyan Multi-Herbal Composition (CareVid™): In Vitro and In Silico Contrast - Winnie Rotich; Nicholas J. Sadgrove; Eduard Mas-Claret; Guillermo F. Padilla-González; Anastasia Guantai; Moses K. Langat (MDPI AG, 2021)
CareVid is a multi-herbal product used in southwest Kenya as an immune booster and health tonic and has been anecdotally described as improving the condition of HIV-positive patients. The product is made up of roots, barks and whole plant of 14 African medicinal plants: Acacia nilotica (L.) Willd. ex Delile (currently, Vachelia nilotica (L.) P.J.H Hurter & Mabb.), Adenia gummifera (Harv.) Harms, Anthocleista grandiflora Gilg, Asparagus africanus Lam., Bersama abyssinica Fresen., Clematis hirsuta Guill. & Perr., Croton macrostachyus Hochst. ex Delile, Clutia robusta Pax (accepted as Clutia kilimandscharica Engl.), Dovyalis abyssinica (A. Rich.) Warb, Ekebergia capensis Sparm., Periploca linearifolia Quart.-Dill. & A. Rich., Plantago palmata Hook.f., Prunus africana Hook.f. Kalkman and Rhamnus prinoides L'Her. The objective of this study was to determine the major chemical constituents of CareVid solvent extracts and screen them for in vitro and in silico activity against the HIV-1 reverse transcriptase enzyme. To achieve this, CareVid was separately extracted using CH2Cl2, MeOH, 80% EtOH in H2O, cold H2O, hot H2O and acidified H2O (pH 1.5-3.5). The extracts were analysed using HPLC-MS equipped with UV diode array detection. HIV-1 reverse transcriptase inhibition was performed in vitro and compared to in silico HIV-1 reverse transcriptase inhibition, with the latter carried out using MOE software, placing the docking on the hydrophobic pocket in the subdomain of p66, the NNRTI pocket. The MeOH and 80% EtOH extracts showed strong in vitro HIV-1 reverse transcriptase inhibition, with an EC50 of 7 μg·mL−1. The major components were identified as sucrose, citric acid, ellagic acid, catechin 3-hexoside, epicatechin 3-hexoside, procyanidin B, hesperetin O-rutinoside, pellitorine, mangiferin, isomangiferin, 4-O-coumaroulquinic acid, ellagic acid, ellagic acid O-pentoside, crotepoxide, oleuropein, magnoflorine, tremulacin and an isomer of dammarane tetrol. Ellagic acid and procyanidin B inhibited the HIV-1 reverse transcription process at 15 and 3.2 µg/mL−1, respectively. Docking studies did not agree with in vitro results because the best scoring ligand was crotepoxide (ΔG = −8.55 kcal/mol), followed by magnoflorine (ΔG = −8.39 kcal/mol). This study showed that CareVid has contrasting in vitro and in silico activity against HIV-1 reverse transcriptase. However, the strongest in vitro inhibitors were ellagic acid and procyanidin B.